As pedras do caminho, de Lydia Mombelli da Fonseca : do apagamento à investigação acadêmica - Modelski, Jaqueline (My University, 2016)
The present dissertation consists on the analysis of the novel The stones of the road (As pedras do caminho), by the female gaucho writer Lydia Mombelli da Fonseca, with regard to the literary research of the representation of the female subject, based on theoretical framework of cultural studies of gender, feminist criticism and regionality, patriarchal ideology and identity. In this sense, it is possible to observe the role relating to women in society, especially in the decade of 1950, the year of publication of the novel, in order to unveil stigmas and behaviors expected of women at the time, in addition to promoting reflections on established and reproduced social naturalizations in relation to the female subject, even amidst the present. Furthermore, this study seeks to demonstrate the participation of women as the subject of historical and cultural process as a producer of literary text, bringing to academic knowledge the author Lydia Mombelli da Fonseca, in order to contribute to the expansion of the cultural and literary history of the Italian Colonization Region of Rio Grande do Sul and the state itself.
A presente dissertação consiste na análise da obra As pedras do caminho, da escritora gaúcha Lydia Mombelli da Fonseca, no tocante à investigação literária da representação do sujeito feminino, com base em aporte teórico de estudos culturais de gênero, crítica feminista, bem como regionalidade, ideologia patriarcal e identidade. Nesse sentido, observa-se o papel referente à mulher na sociedade, principalmente, por volta da década de 1950, ano de publicação do romance, com o objetivo de desvelar estigmas e comportamentos esperados das mulheres na época, além de promover reflexões a respeito de naturalizações sociais estabelecidas e reproduzidas em relação ao sujeito feminino, ainda, em meio à contemporaneidade. Ademais, este estudo busca demonstrar a participação da mulher como sujeito do processo histórico-cultural enquanto produtora de texto literário, trazendo ao conhecimento acadêmico a autora Lydia Mombelli da Fonseca, a fim de contribuir para o alargamento da história cultural e literária da Região de Colonização Italiana do Rio Grande do Sul e do próprio estado.
Keywords: As pedras do caminho (Obra literária); Identidade; Mulheres - Identidade; Mulheres na literatura; Regionalismo na literatura; Literatura sul-rio-grandense - Crítica e interpretação; Fonseca, Lydia Mombelli da, 1912-2000; Women - Identity; Women in literature; Regionalism in literature; The stones of the road (Literary work); Identity; Feminist criticism